PENGARUH HIGH PERFORMACE WORK SYSTEM DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP PERCEIVED WORKLOAD MELALUI PSYCHOLOGICAL EMPOWERMENT KARYAWAN PT. BANK ACEH SYARIAH BANDA ACEH - Khalil Gibran Putra Phonteuka; Hamdi Harmen (Departemen Manajemen, 2023)
Abstract: This study aims to determine the effect of high performance work systems and perceived organizational support on perceived workload through the Psychological Empowerment of Bank Aceh Syariah Banda Aceh Employees. This research is a quantitative research, collecting data using a questionnaire as an instrument. The population in this study were Bank Aceh Syariah Banda Aceh employees, totaling 2,032 people. as a sample that represents the study population. The sampling technique used is Proportionet Stratified Random Sampling. The data analysis method used is Statistical Product and Service Solutions (SPSS) used as an analytical method to determine the effect of the variables involved. Based on the results of the study found that high performance work systems, perceived organizational support and Psychological Empowerment directly have a significant effect on perceived workload. The results of the study also found that high performance work systems and perceived organizational support also had an effect on the mediator variable, namely Psychological Empowerment, so that Psychological Empowerment was able to become a mediator on high performance work systems and perceived organizational support for perceived workload. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh high performance work system dan perceived organizational support terhadap perceived workload melalui Psychological Empowerment Karyawan Bank Aceh Syariah Banda Aceh. Penelitian ini adalah penelitian kuantitatif, pengumpulan data menggunakan kuesioner sebagai instrument. Populasi dalam penelitian ini adalah Karyawan Bank Aceh Syariah Banda Aceh yang berjumlah 2.032 orang. sebagai sampel yang mewakili populasi penelitian. Teknik pengambilan sampel yang digunakan adalah Proportionet Stratified Random Sampling. Metode analisis data yang digunakan adalah Statistical Product and Service Solutions (SPSS) digunakan sebagai metode analisis untuk mengetahui pengaruh antar variabel-variabel yang terlibat. Berdasarkan Hasil penelitian menemukan bahwa high performance work system, perceived organizational support dan Psychological Empowerment secara langsung berpengaruh signifikan terhadap perceived workload. Hasil penelitian juga menemukan bahwa high performance work system dan perceived organizational support juga berpengaruh terhadap variabel mediator ialah Psychological Empowerment, sehingga Psychological Empowerment mampu menjadi mediator pada high performance work system dan perceived organizational support terhadap perceived wrkload